STRATEGIES OF PT. PEGADAIAN TO ENHANCE MIKRO FIDUSIA SYARIAH CREDIT PERFORMANCE - Wijaya, Ning Karna (al-Uqud : Journal of Islamic Economics, 2019)
This paper aims to find out the strategies of PT. Pegadaian as well as its effectiveness to enhance mikro fidusia syariah credit performance. It uses qualitative descriptive method through secondary data analysis of annual report PT. Pegadaian 2016-2017. Strategy is analyzed by qualitative data while its effectiveness is measured by quantitative data through comparison of Mikro Fidusia Syariah performance target and realization. The result shows that PT. Pegadaian strategies, such as product service channel reinforcement (collection), establishment sales force inorganic team, idle asset optimization, and establishment of Appraisal Officer Profession Certification Institution, have been implemented effectively to reach mikro fidusia syariah credit performance target 2016-2017. It is shown by customer number growth, number of transaction, sales turnover, outstanding loan, and munah that exceed 100% in average. However, that strategy is less effective to maintain the achievement in 2017, its effectiveness is lower than 2016.